(untitled) (Texas Journal of Engineering and Technology, 2025)
Modern air combat environments are becoming increasingly hostile due to rapid advancements in radar, infrared (IR), and multi-spectral detection technologies. As a result, aviation decoy targets have become indispensable elements of aircraft survivability strategies. These devices, which include both towed and expendable variants, are designed to mislead enemy detection systems and intercept incoming threats. However, their operational performance is often limited by technical and tactical challenges, such as insufficient signal fidelity, limited adaptability to evolving threats, and integration issues with on-board electronic warfare (EW) systems. It presents a comprehensive examination of the challenges associated with the development and deployment of aviation decoy targets. A multi-layered research methodology involving system-level engineering analysis, digital modeling, and review of defense field data is employed to assess current decoy technologies. Key problems, such as reduced efficiency in harsh environmental conditions and vulnerability to advanced missile guidance systems, are identified and addressed. The findings suggest that significant improvements in decoy performance can be achieved through the use of adaptive emission algorithms, and modular hardware designs that allow better integration with the host aircraft’s EW suite. Case studies and simulation results support the proposed enhancements, demonstrating a measurable increase in aircraft survivability rates in complex threat environments. It concludes with a roadmap for future decoy development, emphasizing the need for collaborative international research, rapid prototyping, and real-time threat adaptation. These improvements are vital for maintaining air superiority and protecting high-value aerial assets in contested airspace.